The Heidelberg Catechism and the church - E. A. J. G. van der Borght (Acta Theologica)
What is the ecumenical potential and what are the limitations of the teaching on the church in the Heidelberg Catechism 450 years after its publication? This contribution provides an analysis of the only two Questions/Answers in the HC that specifically deal with ecclesiology. It also searches for references to ministry. After comparing with other, much more elaborate expositions of the theological meaning on the church in catechisms written by members of the drafting team of the HC, the article puts the HC ecclesiology in historical perspectives and explains its conciseness on the issue. After describing more recent interpretations of the teaching of the church in the HC, the text offers a list of ecumenical potentials and limitations.